2012
DOI: 10.1002/clc.22056
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rate Increases Steeply With Nonadherence to Statin Therapy in Patients With Acute Coronary Syndrome

Abstract: Background: In a prospective cohort of consecutive acute coronary syndrome (ACS) patients, we compared the adherence rate of statin usage and mortality rate during a median follow-up of 23 months. Hypothesis: Adherence to statin therapy after acute coronary syndrome affects mortality rate. Results: At discharge, the rate of statin prescription to patients was 95.4% (n = 1878). When comparing adherent patients (n = 1200; 61.7%), who purchased the medication systematically until the end of the median 23-month fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…6 7 9-12 Non-adherence, however, translates into poor clinical outcomes. [12][13][14][15] Understanding the reasons for non-adherence, therefore, can inform development of technological methods to improve adherence. Insufficient knowledge about medication regimens, low motivation or forgetfulness, polypharmacy, adverse side effects, increasing age and a lack of practical support have all been implicated and may be borne in mind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 7 9-12 Non-adherence, however, translates into poor clinical outcomes. [12][13][14][15] Understanding the reasons for non-adherence, therefore, can inform development of technological methods to improve adherence. Insufficient knowledge about medication regimens, low motivation or forgetfulness, polypharmacy, adverse side effects, increasing age and a lack of practical support have all been implicated and may be borne in mind.…”
Section: Discussionmentioning
confidence: 99%
“…Increased mortality is associated with poor β-blocker or clopidogrel adherence at 1 year (2.6-fold increased mortality or non-fatal myocardial infarction), and statins and β-blockers in the longer-term (median 2.4 years of follow-up) 512–14 In addition, over median follow-up of 23 months, a prospective cohort study using the Finnish Prescription Register demonstrated a dose–response relationship between (1) regular (2) irregular or (3) no statin use and mortality (4.9%, 9.4% and 14.9%, respectively), and cardiovascular death in particular (2.9%, 5.1% and 7.4%) 14. Non-adherence to dual antiplatelet therapy (aspirin and clopidogrel) after stent implantation also poses the added risk of potentially catastrophic stent thrombosis 15…”
Section: Extent Of Non-adherencementioning
confidence: 99%
“…However, good adherence to therapy further reduced mortality risk (4Á9% vs. 14Á9%; P < 0Á001). Moreover, this study has pointed that earlystarted statin therapy (within 7 days from admission) reduces by twofold the mortality risk (HR 2Á34 [95% CI 1Á19-4Á89]; P = 0Á01) [20]. On the other hand, the Platelet Receptor Inhibition in Ischemic Syndrome Management (PRISM) study first investigated the effects of statin therapy discontinuation at 30-day follow-up in patients admitted for ACS [17].…”
Section: Timing Of Statin Administrationmentioning
confidence: 98%
“…Table 1 summarizes the results of relevant clinical trials and registries analysis [15][16][17][18][19][20]. The Myocardial Ischemia Reduction with Aggressive Cholesterol Lowering (MIRACL) study is the first large study investigating the potential clinical benefit of the early use of statins in ACS [15].…”
Section: Timing Of Statin Administrationmentioning
confidence: 99%
“…[7][8][9][10] There have been fewer studies on unintentional nonadherence caused by doctors. Lopez-Carmona et al performed an epidemiological study in Spain where they found a significant gap between current guidelines on recommended prescriptions and clinical practice to make these prescriptions.…”
Section: Next Stepmentioning
confidence: 99%